Strategi Adaptasi dan Inovasi Kurikulum Pendidikan Islam di Era Digital 4.0 - Akhyar, Muaddyl; M, Iswantir; Febriani, Susanda; Gusli, Ramadhoni Aulia (Instructional Development Journal, 2024)
Nowadays, industrial progress has demanded society to be able to handle all problems, especially in the field of education. In the era of the industrial revolution 4.0, educational institutions face great challenges to address the problems and changes that arise in people's lives to prevent the negative impact of rapid progress. The 4.0 revolution is characterised by the rapid advancement of science and technology, which has led to major breakthroughs for society. Some people become motivated and able to develop science and produce new innovations to meet the needs of society in various fields, including in the field of education. This research uses a library research approach or literature study, where data sources are examined with references to books, articles, previous research journals, and other scientific works related to the adaptation and innovation strategies of the Islamic education curriculum in the digital 4.0 era. The results show that Islamic education may be able to re-explore the ability to recognise all the potential it has, and then equip it with availability.